Analysis Of The Role Of Civil Servant Investigators Of The Sea and Coast Guard Base In Law Enforcement Shipping Crime: Research Study At Class II Tanjung Uban PLP Base - Bagus Riadi; Erniyanti Erniyanti; M. Soerya Respationo; Darwis Anatami; Ramlan Ramlan (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2024)
Law enforcement in the shipping sector is an important aspect in maintaining security and order in Indonesian waters. Civil Servant Investigators (PNS) at the Marine and Coast Guard Base (PLP) have a central role in cracking down on shipping crimes. This study aims to analyze the role of civil servant investigators at the Tanjung Uban Class II PLP Base in law enforcement of shipping crimes, identify the obstacles faced, and provide recommendations to increase the effectiveness of law enforcement. The research methods used are normative juridical and empirical sociology. Normative juridical research is carried out through the study of relevant documents and laws and regulations, such as Law Number 17 of 2008 concerning Shipping and its implementing regulations. Empirical sociological research was conducted through interviews with civil servant investigators, related parties, and analysis of concrete cases handled at the Tanjung Uban Class II PLP Base. The results of the study show that civil servant investigators at the Tanjung Uban Class II PLP Base have an important role in law enforcement of shipping crimes, but face various obstacles. Limited human resources and facilities, lack of coordination between agencies, and technical and legislative obstacles are some of the main obstacles. Case handling such as KM. Putra Harapan Baru and MT. Queen Majesty revealed that violations often occur due to non-compliance with shipping regulations, as well as a lack of legal awareness among shipping industry players. Based on the results of the research, it is recommended that the number and quality of investigators be increased through training and recruitment, investment in adequate facilities and equipment, and increased coordination between agencies. In addition, the adjustment of domestic regulations to international standards and legal awareness campaigns for the public and shipping industry players are also important to ensure compliance with the law. Strengthening legal protection for investigators from external intervention and strict enforcement of the code of ethics will help maintain integrity and professionalism in maritime law enforcement. With this effort, it is hoped that law enforcement of shipping crimes at the Tanjung Uban Class II PLP Base can run more effectively and efficiently.